Pregnancy after in vitro fertilization in an elderly primigravida with Shereshevsky-Turner Syndrome: A case report - Perizat Saparbaevna Sadykova; Sholpan Kuanyshbekovna Sarmuldayeva; Galina Kalievna Kausova; Elvira Shukenova; Linas Rovas (Shahid Sadoughi University of Medical Sciences, 2023)
Abstract Background: Shereshevsky-Turner Syndrome is a chromosomal condition that affects females owing to full or partial missing of X-monosomy in all or part of the body's cells. Shereshevsky-Turner Syndrome is characterized by severe hormonal disorders and defects of the cardiovascular and urinary systems. With the advent of assisted reproductive technology (ART), pregnancy has become more accessible for this group of cases, often with donor eggs. In the available literature, it was not possible to find exact information during the time of selection of progestogen support, the duration of the appointment, and the term of withdrawal. Case presentation: This is the case of a 36-yr-old primigravid woman suffering from STs, mosaic karyotype comprising of 3 clones: 45X (69), 46XX (23), 47XXX (8), and 1000 interphase nuclei. In this case, we left high-maintenance doses of progesterone due to the application of ART and concomitant extragenital pathology, leading to a decrease in all functions of the placenta, including the endocrine. The woman was monitored before, during, and after the pregnancy. She was delivered at 37 wk and 6 days of gestation. Conclusion: ART increases the possibility of having a pregnancy and gestation in cases with a wide variety of genital and extragenital pathologies.